Hepato-Safety Effect of the Poly-Herbal Aqueous Extract Using Animal Model - Gabriel, Benjamin Ogunma; Uwaokhonye, Christabel Osemudiame; Oshomoh, Emmanuel Ola (African Journal of Sciences and Traditional Medicine, 2024)
Poly-herbal formulation has been used all around the world due to its medicinal and therapeutic applications. These effects encompass mutual enhancement, mutual assistance, mutual restraint, and mutual antagonism.This research investigated the impact of a poly-herbal aqueous extract on the liver protective effect in Wistar rats. Plant samples were collected and processed into an extract. Twenty Wistar rats were divided into control group and graded doses (200, 400, and 800 mg/kg) of the poly-herbal aqueous extract. The rats were orally administered graded doses of the extract for 28 days. Various hepatic function tests (Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), Alkaline Phosphatase (ALP), Total Bilirubin, Conjugated Bilirubin, Albumin, and Total Protein), were evaluated using standard protocol. The results indicated a significant increase in Aspartate Aminotransferase, total protein, and Globulin levels across the different doses when compared to the control group. A decrease in the Alkaline Phosphatase levels across the lowest doses. A significant decrease in Alanine Transferase, Total Bilirubin, Conjugated Bilirubin, and Albumin levels was observed across graded doses compared to the control group. In conclusion, this finding agreed with the report of the folklore findings on the poly-herbal aqueous extract with hepato-protective effect.